2019
DOI: 10.1074/jbc.ra118.004736
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the CORVET complex alleviates the fungicidal effects of fludioxonil on the yeast Saccharomyces cerevisiae expressing hybrid histidine kinase 3

Abstract: Increased accumulation of glycerol and the nuclear translocation of Hog1p are not essential for fludioxonil toxicityActivation of the HOG/p38 pathway causes increased synthesis and accumulation of glycerol in the cell as a part of the 462 Role of CORVET complex in fungicidal action of fludioxonil

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Glycerol accumulation is a natural response of the cellular adaptation to some stresses such as high osmolarity and salt. However, over‐accumulation of intracellular glycerol may cause cell swelling, thereby leading to various morphological defects and ultimately growth inhibition (Randhawa et al , 2019). The data herein revealed that the normal degradation processes of glycerol were broken in the Δ VdAtf1 strain, presumably due to the downregulation of transcription of certain genes encoding key enzymes in glycerol catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol accumulation is a natural response of the cellular adaptation to some stresses such as high osmolarity and salt. However, over‐accumulation of intracellular glycerol may cause cell swelling, thereby leading to various morphological defects and ultimately growth inhibition (Randhawa et al , 2019). The data herein revealed that the normal degradation processes of glycerol were broken in the Δ VdAtf1 strain, presumably due to the downregulation of transcription of certain genes encoding key enzymes in glycerol catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Single deletion of VdSkn7 or double deletion of VdAtf1 and VdYap1 leads to its up‐regulation, causing abnormal glycerol accumulation. Over‐accumulation of intracellular glycerol may cause cell swelling, thereby leading to various morphological defects and ultimately growth inhibition (Randhawa et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Over-accumulation of glycerol in the cell may lead to various morphological defects and ultimately growth inhibition, though its normal accumulation is a cellular adaptation to high osmotic stress and salt stress ( Randhawa et al, 2019 ). Fungi must maintain glycerol levels within limits suitable for growth, and tightly control its production and suppression ( Kayingo et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%